(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical and paraclinical characteristics, treatment outcomes of infants born before 32 weeks’ gestation, and to identify factors associated with necrotizing enterocolitis. Research methods: A cross-sectional study was conducted on 124 neonates aged under 28 days with gestational age at birth < 32 weeks who were admitted to the Pediatrics Center, Bach Mai Hospital from April 2024 to April 2025. Clinical and laboratory manifestations were collected. Treatment methods (medications, procedures) and care outcomes were recorded. Results: Male infants accounted for 54.8%. Common clinical symptoms included respiratory distress (95%), prolonged capillary refill time > 3 seconds (33.9%), feeding intolerance (28.2%), hypotension (24%), hypothermia (20.2%). Frequent paraclinical abnormalities included coagulopathy (55.6%), hypoglycemia (48.4%), thrombocytopenia (37.9%), and hypoalbuminemia (33.1%). Prematurity-related complications were neonatal sepsis (71.8%), hemodynamically significant patent ductus arteriosus (29%), necrotizing enterocolitis (28.2%), bronchopulmonary dysplasia (22.5%), and intraventricular hemorrhage of various grades (21.8%). The overall mortality rate was 24.2%, with mortality rates of 71.4% among infants < 28 weeks and 18.2% among those 28-32 weeks. Factors associated with increased risk of necrotizing enterocolitis included gestational age at birth (p = 0.023), intrauterine growth restriction (OR = 4.668; 95% CI = 1.805-12.073; p = 0.001), hypothermia (OR = 5.318, 95% CI = 2.119-13.347; p < 0.001), and hemodynamically significant patent ductus arteriosus (OR = 4.176, 95% CI = 1.802-9.682; p = 0.000). Conclusion: Mortality and complication rates among infants born before 32 weeks remain high, underscoring the need for improved prenatal management and effective neonatal care strategies. Gestational age, intrauterine growth restriction, hypothermia, and hemodynamically significant patent ductus arteriosus are important risk factors for necrotizing enterocolitis in this population.